2014
DOI: 10.1093/gerona/glu221
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Endurance Training on Mitochondrial Protein Damage, Degradation, and Acetylation in the Context of Aging

Abstract: Acute aerobic exercise increases reactive oxygen species and could potentially damage proteins, but exercise training (ET) enhances mitochondrial respiration irrespective of age. Here, we report a differential impact of ET on protein quality in young and older participants. Using mass spectrometry we measured oxidative damage to skeletal muscle proteins before and after 8 weeks of ET and find that young but not older participants reduced oxidative damage to both total skeletal muscle and mitochondrial proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 50 publications
(69 reference statements)
9
80
0
1
Order By: Relevance
“…Future studies should focus on the relationship between exercise intensity and oxidative stress in the elderly, and the relationship between different types of exercise (aerobic, anaerobic or mixed) and oxidative stress in this population. [25,26,113]. These studies found that endurance training attenuated resting and exerciseinduced oxidative stress, and increased protection against oxidative stress by increasing the efficiency of enzymatic and non-enzymatic antioxidant defence systems, suggesting training-induced adaptations of oxidative stress.…”
Section: Oxidative Stress and Acute Exercise In Elderly Subjectsmentioning
confidence: 84%
“…Future studies should focus on the relationship between exercise intensity and oxidative stress in the elderly, and the relationship between different types of exercise (aerobic, anaerobic or mixed) and oxidative stress in this population. [25,26,113]. These studies found that endurance training attenuated resting and exerciseinduced oxidative stress, and increased protection against oxidative stress by increasing the efficiency of enzymatic and non-enzymatic antioxidant defence systems, suggesting training-induced adaptations of oxidative stress.…”
Section: Oxidative Stress and Acute Exercise In Elderly Subjectsmentioning
confidence: 84%
“…Detected PTMs were attested following previously published guidelines (11). Relative expression of protein PTMs (at sample level) between two groups was performed using peptide intensities as described previously (24) and then displayed as percent difference between study days.…”
Section: Methodsmentioning
confidence: 99%
“…An acute endurance exercise programme up‐regulated proteins involved in activation of the electron transport chain components such as mitochondrial SIRT3, as well as mitochondrial antioxidant capacity, in older adults (>65 years) (Johnson et al . ). Nevertheless, elevated protein degradation and reduced oxidative damage were only observed in the young, suggesting age‐specific effects (Johnson et al .…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, elevated protein degradation and reduced oxidative damage were only observed in the young, suggesting age‐specific effects (Johnson et al . ). In contrast, 12 weeks of aerobic exercise intervention in 20‐ and 70‐year‐old participants resulted in increased aerobic capacity, skeletal muscle size and markers of mitochondrial biogenesis and dynamics in both groups (Konopka et al .…”
Section: Introductionmentioning
confidence: 97%